07 FAKTOR-FAKTOR YANG MEMPENGARUHI PERANAN KELOMPOK TANI DALAM MENINGKATKAN PENDAPATAN USAHA TANI PADI SAWAH IRIGASI DUSUN SEGE-SEGERI, DESA MINASABAJI - Jurnal Agribis; Firdayani Muhammad; Zulkifli Zulkifli; Andi Nur Imran (Universitas Muslim Maros, 2020)
This research was conducted in Sege-segeri Hamlet, Minasa baji Village, Kec. Bantimurung Kab. Maros. This location was chosen with the consideration that it has long been managing rice crops. The data used are primary data and secondary data. The data collection technique used the interview method, the observation and the questionnaire method, the data analysis method used the multiple linear regression formula. The results showed that farmer groups in Sege-segeri Hamlet played a role in the income of irrigated rice farming in Sege-Segeri Hamlet, Minasa Baji Village, Bantimurung District, Maros Regency. The purpose of this study was to see whether the farmer groups who conduct study classes, cooperation vehicles and production units have an effect on farmers' income. Data were collected from the survey results using a questionnaire and supplemented with field observations. The data that has been collected is then used to obtain real data for analysis purposes. This study uses multiple linear regression methods to determine whether the learning class, cooperation vehicle and production unit affect the opinion of farmers in Sege-Segeri Hamlet, Minasa Baji Village. The results of this research can be carried out in Sege-Segeri Hamlet, Minasa Baji Village, Bantimurung District, Maros Regency and the results of this study are 0.835 learning class, 0.636 cooperative vehicle and 0.906 production unit which means it affects farmers' income.